2010
DOI: 10.1677/joe-10-0342
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and dopamine receptor interaction in prostate and lung cancer cell lines

Abstract: Somatostatin analogues inhibit in vitro cell proliferation via specific membrane receptors (SSTRs). Recent studies on transfected cell lines have shown a ligand-induced formation of receptor dimers. The aim of this study is 1) to evaluate the role of specific ligands in modulating receptor interactions in the androgen-dependent prostate cancer cell line, LNCaP, and in the non-small cell lung cancer line, Calu-6, by co-immunoprecipitation and immunoblot; and 2) to correlate the antiproliferative effect of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…These results were confirmed in non-endocrine tumor cells, natively expressing SST receptors and D2R. It was shown that these receptors can interact in the absence of agonists [55] and the treatment with the chimeric compound targeting both receptor types (BIM-23A760) significantly increased the sst5/D2R and sst2/D2R dimers. …”
Section: Somatostatin Receptor Signal Transduction Homo- and Hetementioning
confidence: 60%
“…These results were confirmed in non-endocrine tumor cells, natively expressing SST receptors and D2R. It was shown that these receptors can interact in the absence of agonists [55] and the treatment with the chimeric compound targeting both receptor types (BIM-23A760) significantly increased the sst5/D2R and sst2/D2R dimers. …”
Section: Somatostatin Receptor Signal Transduction Homo- and Hetementioning
confidence: 60%
“…However, these results were obtained in non-pituitary cell lines (CHO or HEK293) stably expressing exogenous receptors, and there is so far no evidence for receptor dimerization in pituitary cells. Recently, somatostatin and D 2 receptors interaction has been demonstrated in prostate cancer cell line, LNCaP, and in non-small cell lung cancer line, Calu-6 (Arvigo et al, 2010). Postreceptor mechanisms involved in the enhanced potency following receptor dimer activation have not yet been characterized.…”
Section: Gh Secretion and Gh Mrna Expressionmentioning
confidence: 99%
“…Over the past several years, evidence that dopamine receptors are expressed in cancer cells outside the nervous system has been increasing. DRD2 expression has been found in abnormally proliferating Jurkat cells, prostate cancer lines (LnCAP), and lung cancer stem cells (Arvigo et al, 2010;Basu et al, 2010;Yeh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%